2, 9-Dibenzo[b, def]chrysene as a building block for organic electronics. Issue 1 (24th November 2021) - Gagnon, Félix; Tremblay, Vicky; Soldera, Armand; Ocheje, Michael U.; Rondeau-Gagné, Simon; Leclerc, Mario; Morin, Jean-François
Abstract : A new series of three donor–acceptor conjugated polymers based on a low-cost, easily accessible vat dye called Vat orange 1 have been prepared. The polymers have bandgap values ranging from 1.61 to 1.86 eV. Abstract : In this article, a new series of conjugated polymers based on a low-cost, easily accessible vat dye called Vat orange 1 or 2, 9-dibromo-dibenzo[ b, def ]chrysene-7, 14-dione have been prepared. This compound was made electron-donating by reducing and alkylating the ketone groups into alkoxy groups, allowing the introduction of solubilizing, branched alkyl chains at the 7 and 14 positions. Polymerization reactions using Suzuki–Miyaura coupling with 6, 6′-isoindigo, 3, 6-di-2-thienyl-pyrrolo[3, 4- c ]pyrrole-1, 4-dione (DPP) and 4, 7-dithieno-2, 1, 3-benzothiadiazole (TBT) yielded three donor–acceptor polymers with bandgap values ranging from 1.61 to 1.86 eV. Field-effect transistors (OFETs) and organic solar cells (OSCs) were fabricated and hole mobility values of up to 3.62 × 10 −4 cm 2 V −1 s −1 and a maximum power conversion efficiency of 1.2% were measured, respectively.